Accuracy of stereotaxic localisation using MRI and CT. Issue 12 (December 1986) - Wyper, D J; Turner, J W; Patterson, J; Condon, B R; Grossart, K W; Jenkins, A; Hadley, D M; Rowan, J O
Abstract : The accuracy of stereotaxic coordinates determined using the Leksell apparatus with CT and MRI was investigated using an Agar filled head phantom. Both imaging techniques were found to produce an accuracy of better than 2 mm with the exception of the Z coordinate as measured by CT (2.3 mm). This latter error is greater because of the 3 mm slice width used. Direct coronal views were used to determine Z more accurately using MRI. The measurement procedures are described and it is shown that the Leksell system of using orthogonal coordinates enables the scaling of images, which is particularly necessary with MRI, to be done easily.